2020
DOI: 10.3389/fmicb.2020.564579
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gut Microbiota and Fecal Metabolites Related With the Clinical Subtypes of Myasthenia Gravis

Abstract: Myasthenia gravis (MG) is a devastating acquired autoimmune disease. Previous studies have observed that disturbances of gut microbiome may attribute to the development of MG through fecal metabolomic signatures in humans. However, whether there were differential gut microbial and fecal metabolomic phenotypes in different subtypes of MG remains unclear. Here, our objective was to explore whether the microbial and metabolic signatures of ocular (OMG) and generalized myasthenia gravis (GMG) were different, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Based on a previous finding proposed by Tan et al. that different subtypes of MG have different microbiota composition patterns ( 72 ), we can speculate that fecal metabolites were different among different subtypes. Overall, all the above mentioned studies demonstrated the presence of dysregulated gut microbiota and microbial metabolites in patients with MG, thus providing a new entry point into the pathogenesis of MG and helping us understand the full picture of myasthenia gravis to propose new therapeutic strategies.…”
Section: Dysbiosis Of Gut Microbiota and Microbial Metabolites In Patients With Mgmentioning
confidence: 66%
See 1 more Smart Citation
“…Based on a previous finding proposed by Tan et al. that different subtypes of MG have different microbiota composition patterns ( 72 ), we can speculate that fecal metabolites were different among different subtypes. Overall, all the above mentioned studies demonstrated the presence of dysregulated gut microbiota and microbial metabolites in patients with MG, thus providing a new entry point into the pathogenesis of MG and helping us understand the full picture of myasthenia gravis to propose new therapeutic strategies.…”
Section: Dysbiosis Of Gut Microbiota and Microbial Metabolites In Patients With Mgmentioning
confidence: 66%
“…A study aimed to identify the distinctive gut microbes in different subtypes of MG showed that patients with GMG harbored lower community richness and diversity and more severe gut microbial disturbances than patients with OMG. Compared with HCs, the families of Bacteroidaceae and Veillonellaceae were significantly more abundant, whereas families of Lachnospiraceae, Erysipelotrichaceae, Ruminococcaceae, Peptostreptococcaceae, Coriobacteriaceae, and Clostridiaceae_1 were scarcer in patients with MG ( 72 ). According to published literature, previous studies have suggested that Veillonellaceae and Bacteroidales are positively correlated with certain autoimmune disorders, whereas Ruminococcaceae and Lachnospiraceae, the common short chain fatty acids (SCFAs) producers ( 73 ), are negatively correlated with these diseases ( 74 , 75 ).…”
Section: Dysbiosis Of Gut Microbiota and Microbial Metabolites In Patients With Mgmentioning
confidence: 99%
“…This method can detect the microbiome’s genome composition at the species level of bacteria, archaea, fungi, and even viruses and analyze its functional biological characteristics [ 13 ]. Recent studies have reported that the gut microbiota in MG patients is altered compared to healthy people [ 14 , 15 ], and differential gut microbiota and fecal metabolites are related to the clinical subtypes of MG [ 16 ]. However, the studies are based on 16S research focusing on adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…MG is an autoimmune disease characterized by variable muscle weakness, with the primary subtype attributed to antibodies binding to AChR at the NMJ ( 5 , 11 , 12 ). Forkhead box (Fox) P3+ cluster of differentiation (CD) 4+ regulatory T cells (Tregs) play a critical role in maintaining self-tolerance and immune homeostasis to prevent the development of MG ( 12 ); these cells are depleted in MG patients, which may contribute to the pathogenesis of this disorder ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%